(untitled) (Eurasian Research Bulletin, 2022)
The article scrutinizes the latest work and research on the digital economy and its core base – ICT infrastructure. Moreover, the digital economy scope of Uzbekistan has been evaluated based on national and international indica-tors in depth. The article concludes that accelerating the process of digital transformation is inevitably urgent despite the annual growth of national and international scores.